Gancao (Glycyrrhizae Radix) provides the main contribution to Shaoyao-Gancao decoction on enhancements of CYP3A4 and MDR1 expression via pregnane X receptor pathway in vitro - Dandan Feng; Tao Tang; Rong Fan; Jiekun Luo; Hanjin Cui; Yang Wang; Pingping Gan (BMC, 2018)
Abstract Background Chinese herbal formula Shaoyao Gancao decoction (SGD) is often used as an adjuvant with chemotherapeutic agents to treat cancer. Due to the herb-drug interactions, the alternations of drug metabolic enzyme and drug transporters induced by SGD deserve to be explored. We aimed to investigate the effect of SGD on the pregnane X receptor (PXR)-mediated transcriptional regulation of cytochrome P450 3A4 (CYP3A4) and drug transporter multidrug resistance protein 1 (MDR1) in vitro. Besides, we assessed the contribution of constituent herbs to SGD on the regulation of CYP3A4 and MDR1. Methods The dual luciferase reporter gene system containing the hPXR expression plasmid and the reporter gene plasmid of CYP3A4 or MDR1 was co-transfected to HepG2 and Caco2 cells. Luciferase activities were determined using a Dual-luciferase reporter assay kit. The gene expression of CYP3A4 and MDR1 in the hPXR-transfected LS174T cells were assessed by real-time qPCR. Finally, the contribution of constituent herbs from SGD was evaluated. Results SGD, Shaoyao and Gancao concentration-dependently increased promoter activities of CYP3A4 and MDR1 in vitro. Moreover, SGD, Shaoyao and Gancao up-regulated CYP3A4 and MDR1 mRNA in hPXR-transfected LS174T cells. As the herbal constituent of SGD, Gancao possesses significantly higher levels of metabolic enzyme and drug transporters compared with Shaoyao. Conclusion SGD tends to enhance CYP3A4 and MDR1 expression via PXR pathway, especially Gancao provides the main contribution. This study highlights a potential in vitro mechanism for SGD on the regulation of drug metabolic enzymes and drug transporters.